A novel approach to the management of carotid blowout syndrome: the use of thrombin in a case of failed covered stenting. (24th February 2016) - Sablani, Naveen; Jain, Gary; Hasan, Maryam Mumtaz; Sivakumar, Keithan; Feuerwerker, Solomon; Arcot, Karthikeyan; Farkas, Jeffrey
Abstract : Acute hemorrhage relating to an expanding pseudoaneurysm of the carotid artery is referred to as carotid blowout syndrome (CBS). CBS is associated with a high morbidity and mortality. We describe the case of a patient who presented with dysphagia and a pulsatile mass in the neck. Imaging revealed a pseudoaneurysm originating from the bifurcation of the distal right common carotid artery. On neuroangiography the patient lacked sufficient collaterals to allow for vessel sacrifice. A decision was made to use covered stents to prevent flow into the pseudoaneurysm while maintaining vessel patency. Despite placement of multiple covered stents there was residual slow filling of the pseudoaneurysm. We augmented this therapy with direct percutaneous thrombin injection into the pseudoaneurysm. This resulted in complete thrombosis of the pseudoaneurysm. For recalcitrant lesions in which the usual methods of stopping blood flow to the pseudoaneurysmal sac fail, an adjuvant approach with thrombin should be considered.